Low-contact-resistance non-gold Ta/Si/Ti/Al/Ni/Ta ohmic contacts on undoped AlGaN/GaN high-electron-mobility transistors grown on silicon - Li, Yang (2015)
Low-contact-resistance (Rc) non-gold Ta/Si/Ti/Al/Ni/Ta ohmic contacts were realized on an undoped AlGaN/GaN high-electron-mobility transistor (HEMT) grown on a silicon substrate. Optimization of the rapid thermal process reveals that Rc decreases drastically from the annealing temperature of 700 to 850 °C and slightly increases from 875 to 900 °C. The sample annealed at 850 °C exhibited the lowest Rc of 0.22±0.03 Ω·mm [specific contact resistivity, ρc=(0.78±0.22)×10-6 Ω·cm2] with a smooth surface morphology (RMS roughness ~5.5 nm). The low Rc is due to the formation of TixSiy and the intermixing of TixSiy with the bottom Ta layer at the metal/semiconductor interface.